Experiences with IL-1 blockade in systemic juvenile idiopathic arthritis - data from the German AID-registry - Elke Lainka; Melanie Baehr; Bernadette Raszka; Johannes-Peter Haas; Boris Hügle; Nadine Fischer; Dirk Foell; Claas Hinze; Elisabeth Weissbarth-Riedel; Tilmann Kallinich; Gerd Horneff; Daniel Windschall; et al. (BMC, 2021)
Abstract Background Systemic juvenile idiopathic arthritis (sJIA) is a complex disease with dysregulation of the innate immune system driven by cytokines. A major role is ascribed to interleukin-1β (IL-1β), supporting the autoinflammatory character of the disease and offering an effective blocking mechanism for treatment. Here we present clinical practice data from the German AID-registry for patients treated with IL-1 inhibition (IL-1i). Methods In 2009 a clinical and research consortium (AID-Net) was established, including an online AID-registry. Patients with documented sJIA diagnosis were identified. Data for this retrospective IL-1i study were recorded by 17 centers. Response to treatment was evaluated according to Wallace criteria and additionally by an own classifying clinical response system. Results In 6 years, 202 patients with confirmed sJIA were recorded in the AID-registry. Out of these, 111 children received therapy with Anakinra (ANA) (n = 84, 39 f) and/or Canakinumab (CANA) (n = 27, 15 f) at a median age of 8.7 y (range 0.6-19.1). During the first 12 months 75/111 (ANA 55, CANA 20) patients were evaluated according to Wallace criteria (achievement of inactive disease 28/55 and 17/20, remission over 6 months under medication 13/55 and 7/20 cases). Over the whole period of time, clinical response was preserved in the majority of patients (ANA 54/80, CANA 20/27). Arthritis mostly persisted in polyarticular (PA) courses. During treatment with IL-1i concomitant medication could be tapered in about 15%. IL-1i was discontinued in 59/111 patients. 45 (15) adverse events (AE)s in ANA (CANA) treated patients (19.7 (26.6) AE/100 ANA (CANA) exposure years, 95%CI: 14.4-26.4 (14.9-43.9)) were reported. Conclusion In a large cohort of sJIA patients from Germany, we can confirm an overall favorable clinical response to both available IL-1 blocking agents. IL-1i was well tolerated with acceptable safety and effectiveness in a real-life clinical setting.